Human environments a cross-cultural encyclopedia - Levinson, David (ABC-Clio, 1995)
Lush tropical rainforest, harsh arctic tundra, and hot, dry desert. While worlds apart in geography and topography, each environment has one common denominator: people. For millions of years humans have adapted to, been influenced by, and influenced their surroundings. This comprehensive volume examines the interesting and varied environments in which humans have survived and often thrived. While the author primarily emphasizes our physical environment - climate, weather, landforms, and natural resources, including plants - he also gives careful consideration to the interrelationships among the physical environment and the biological, socio-cultural, and supernatural environments. A comparison of annual subsistence cycles, patterns of settlement, dwellings, methods used to collect food, beliefs about environmental features, and efforts to control environmental events helps trace the patterns of adaptation and allows readers to understand the role of physical environment in the human experience. Filled with alphabetically arranged, cross-referenced entries with bibliographic citations, this volume, while extensive in scope, extracts the particulars of varied human environments and translates them into terms easily accessible to students. Illustrations, a master bibliography, maps showing the locations of cultures, and a subject index complete the work.
Keywords: Écologie humaine - Encyclopédies; Human ecology -- Encyclopedias; Humanökologie